MITRE Maternal Mortality Interactive Dashboard (3MID): A Data‐Driven Decision Making Tool to Reduce Maternal Death. (20th August 2020) - Mayer, R.; Sheikhnureldin, A.; Comer, K.; Volkin, S.; Klaus, S.
Abstract : To use modeling and simulation to analyze the interplay of factors and interventions on maternal mortality rates and to empower decision makers with the necessary data to make informed decisions to reduce maternal mortality rates, particularly among non‐Hispanic black women. The interactive dashboard is fed by the results of a simulation model—a computer representation of a system meant to observe the effect of changes onto the system through time (ie, dynamic) using a synthetic population. A synthetic population is a reproduced representation of a population (eg, women of childbearing potential) that replicates the statistical variable distributions of a population. With the use of Synthetic Populations and Ecosystems of the World (SPEW), Healthcare Cost and Utilization Project (HCUP), Institute for Health Metrics and Evaluation (IHME), and March of Dimes PeriStats, we sample a synthetic population representing women of childbearing age to assess the risk of maternal mortality at the individual level. Then, users can analyze how budgeting, social determinants of health, and the application of quality improvement toolkits address the leading causes of pregnancy‐related deaths. The toolkits were designed by the California Maternal Quality Care Collaboration (CMQCC) to address conditions such as obstetric hemorrhage and preeclampsia. Various runs of the simulation allow the user to see how the selected interventions might reduce the rates of maternal mortality in various states. Women of childbearing age between the ages of 14 and 44 within the state of California and Georgia to ensure varying economic, racial, and political diversity. The intention is to expand the scope nationally following validation. The MITRE Maternal Mortality Interactive Dashboard (3MID), a microsimulation and policy simulator, allows users to set parameters and evidence‐based interventions to understand the influence and the most impactful interventions to reduce maternal mortality rates, particularly among non‐Hispanic black women. The outputs of a simulation are predicted number of maternal deaths, simulated program cost, and mortality risk assessment score. The risk of mortality is calculated as a linear regression model of the individual's race, age, and county of residence. These results are based off mortality trends derived from high‐level reports from AHRQ that are based on the HCUP data. The 3MID prototype allows users to maximize the allocation of their resources to reduce maternal mortality. This sets the foundation to explore the additional social determinants of health and expand the scope to include severe maternal morbidity, additional variables, and more states. The United States is the only developed nation in the world with an increasing maternal mortality rate. Policy makers currently do not have the data needed to understand the impact of interventions. By using this evidence‐based approach, decision makers can use 3MID to make informed decisions to reduce the maternal deaths within their states and lower the United States' overall maternal mortality rate. ©2020 The MITRE Corporation. ALL RIGHTS RESERVED. This study was supported by the Internal MITRE Research Program.